2018
DOI: 10.1136/neurintsurg-2018-014206
|View full text |Cite
|
Sign up to set email alerts
|

Futile inter-hospital transfer for mechanical thrombectomy in a semi-rural context: analysis of a 6-year prospective registry

Abstract: Background and purposeInter-hospital transfer for mechanical thrombectomy (MT) might result in the transfer of patients who finally will not undergo MT (ie, futile transfers [FT]). This study evaluated FT frequency in a primary stroke center (PSC) in a semi-rural area and at 156 km from the comprehensive stroke center (CSC).MethodologyRetrospective analysis of data collected in a 6-year prospective registry concerning patients admitted to our PSC within 4.5 hours of acute ischemic stroke (AIS) symptom onset, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…Similar rates in CTA performance within 15 min after NCT (at the PSC) were observed between groups. Significantly higher ASPECT scores (at the CSC) were noted in the EVT compared to the No-EVT group [median (IQR): 10 (9-10) vs. 7 (5)(6)(7)(8)(9)(10), p = 0.001]. The rates of CTP mismatch were significantly higher in the EVT compared to the No-EVT group (p < 0.001).…”
Section: Comparison Of Patients Considered Ineligible For Evt After Imentioning
confidence: 95%
See 1 more Smart Citation
“…Similar rates in CTA performance within 15 min after NCT (at the PSC) were observed between groups. Significantly higher ASPECT scores (at the CSC) were noted in the EVT compared to the No-EVT group [median (IQR): 10 (9-10) vs. 7 (5)(6)(7)(8)(9)(10), p = 0.001]. The rates of CTP mismatch were significantly higher in the EVT compared to the No-EVT group (p < 0.001).…”
Section: Comparison Of Patients Considered Ineligible For Evt After Imentioning
confidence: 95%
“…Currently, the operational workflow in most supraregional neurovascular networks (4, 5) entails acute AIS management, including administration of intravenous thrombolysis, at primary stroke centers (PSCs) followed by emergency interhospital patient transfer to comprehensive stroke centers (CSCs) when EVT is required. Although a growing number of studies have dealt with reasons for unsuccessful EVT in patients transferred from PSCs to CSCs (i.e., the "drip-and-ship" strategy) (6) compared to patients directly transferred to the nearest CSC (i.e., the "mothership" strategy) (7,8), little is known regarding factors that determine the decision-making processes for patient-transfer within neurovascular networks. As current EVT registries, including the German Stroke Registry Endovascular Treatment (GSR-ET) (9, 10), only capture data of transferred patients with intention-to-treat with EVT at the CSCs, realworld evidence on patient selection for interhospital transfer are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that 41% of the patients received EVT, which was lower than prior reports showing a treatment rate of 55%-65%. 5,15 Given the later part of our study period overlapped with guideline changes following landmark trials showing the benefits of EVT up to 24 hours, our findings may be a reflection of lower thresholds for accepting patients with LVO in transfer. 20…”
Section: Discussionmentioning
confidence: 91%
“…This is comparable with a recent study from France that found 73 out of 278 (26%) acute stroke patients with LVO had clinical improvement or arterial recanalization after transfer and thus did not receive endovascular therapy. 15 However, their study period predated the landmark trials demonstrating EVT benefits up to 24 hours and they only included patients presenting within 4.5 hours of stroke onset. They found that patients who were not treated with EVT due to clinical improvement or recanalization had better outcomes at 3 months comparing to those not treated due to other reasons (74% vs. 17% mRS 0-2).…”
Section: Discussionmentioning
confidence: 99%
“…15 Another large series in France identified a 45% rate of transfer without resulting in EST. 16 Looking at these so-called futile transfers through the lens of our current reality in the setting of COVID-19, the need to limit or eliminate these occurrences has become exceedingly clear. These are patients who should stay and receive care at local hospitals, and to do so, we must build our systems of care to bring expertise in Vascular Neurology and NeuroImaging to those patients, as discussed below.…”
Section: The True Cost Of Interhospital Transfer Has Become Clearmentioning
confidence: 99%